Representing women, women representing: backbenchers' questions during Prime Minister's Questions, 1979–2010. Issue 2 (1st June 2019) - Bates, Stephen Holden; Sealey, Alison
Abstract : This article investigates linguistic traces of changing trends in the substantive representation of women, as well as broader representational claims related to constituencies, via an analysis of all backbench questions posed during Prime Minister's Questions in the UK House of Commons during 1979–2010. We investigate the impact of sharp increases in female MPs, in particular, left-wing female MPs, and the presence of a left-wing government on MPs' talk about women and about constituencies. We find no evidence of curvilinear trends in talk about women related to changes in government and female parliamentary presence. We also find that female MPs can be considered critical actors with regard to constituency talk.